Neonatal imprinting predetermines the sexually dimorphic, estrogen-dependent expression of galanin in luteinizing hormone-releasing hormone neurons. - Merchenthaler, I (1993)
The incidence of colocalization of galanin (GAL) in luteinizing hormone-releasing hormone (LHRH) neurons is 4- to 5-fold higher in female than male rats. This fact and the finding that the degree of colocalization parallels estradiol levels during the estrous cycle suggest that GAL is an estrogen-inducible product in a subset of LHRH neurons. To analyze further this paradigm we evaluated the effects of gonadectomy and steroid replacement therapy in male and female rats. Ovariectomy resulted in a significant decrease in the number of cells colocalizing LHRH and GAL, whereas estradiol replacement to such animals restored the incidence of colocalization to that observed in controls. In males, however, estradiol treatment failed to enhance the incidence of colocalization of GAL and LHRH, indicating, therefore, that the colocalization of these peptides is gender-determined. This possibility--i.e., gender-specific determination of LHRH neurons coexpressing GAL--was evaluated by neonatal manipulation of hypothalamic steroid imprinting. As mentioned above, male rats did not respond to estrogen or testosterone by increasing GAL/LHRH colocalization as females did. Neonatally orchidectomized rats, whose hypothalami have not been exposed to testosterone during the critical period, when treated with estrogen in adulthood showed an increase in colocalization of GAL and LHRH similar to that seen in female animals. These observations indicate that the colocalization of LHRH/GAL is neonatally determined by an epigenetic mechanism that involves the testis. In summary, this sex difference in the incidence of colocalization of GAL and LHRH represents a unique aspect of sexual differentiation in that only certain phenotypic characteristics of a certain cellular lineage are dimorphic. The subpopulation of LHRH neurons that also produces GAL represents a portion of the LHRH neuronal system that is sexually differentiated and programed to integrate, under steroidal control, a network of LHRH neurons that could synchronize their activity to control the estrous cycle in rats.